[PP.21.05] RELATIONSHIP BETWEEN MICROVASCULAR STRUCTURE AND T REGULATORY LYMPHOCYTES OF SMALL RESISTANCE ARTERIES. (September 2016) - Rossini, C.; Mori, L.; De Ciuceis, C.; Duse, S.; Semeraro, F.; Solaini, L.; E,; Porteri,; Petroboni, B.; Gavazzi, A.; Rosei, C. Agabiti; Castellano, M.; et al.
Abstract : Objective: Recently it has been demonstrated a role for adaptive immunity, particularly for T regulatory lymphocytes (Tregs), in the development of hypertension and in preventing of angiotensin II–induced vascular injury and inflammation in animal models (Barhoumi T et al, Hypertension 2011;57:469–476). However, no data are presently available in human beings about possible relationships between Tregs and microvascular structural alterations. Design and method: In the present study we enrolled 11 normotensive subjects and 8 hypertensive patients undergoing an election surgical intervention. All patients underwent a biopsy of subcutaneous fat during surgery. Subcutaneous small resistance artery structure was assessed by wire myography and media to lumen ratio (M/L) was calculated. W/L of retinal arterioles was obtained by Scanning Laser Doppler Flowmetry. Functional (basal) and structural (total) microvascular density were studied by capillaroscopy before and after venous congestion. No sign of local or systemic inflammation was present in any subjects or patients. We extracted genomic DNA from small resistance arteries and analyzed methylation status of the FoxP3 gene promoter involved in Treg lymphocytes activation. Unmethylated FoxP3 has been demonstrated to be specific for Treg lymphocytes. A peripheral blood sample was obtained before surgery for routine chemistry Results: Results are summarized in the Table. Figure. No caption available. A significant positive correlation was detected between Tregs in small resistance arteries and basal, total and delta gain capillary density in the forearm, whereas no correlations were observed with small resistance artery M/L and retinal arteriole W/L. In addition, a significant inverse correlation was detected between Treg in subcutaneous small vessels and C reactive protein. Conclusions: Our data suggest that Treg lymphocytes detected in subcutaneous small resistance artery wall are related with capillary density and inversely related with inflammatory markers suggesting a protecting role of Treg also, probably, in terms of angiogenetic properties.